Community-Acquired Pneumonia in Sub-Saharan Africa - Aston, Stephen J.; Rylance, Jamie (Seminars in Respiratory and Critical Care Medicine, 2016)
Community-acquired pneumonia (CAP) in sub-Saharan Africa is a common cause of adult hospitalization and is associated with significant mortality. Human immunodeficiency virus (HIV) prevalence in the region leads to differences in CAP epidemiology compared with most high-income settings: patients are younger, and coinfection with tuberculosis and opportunistic infections is common and difficult to diagnose. Resource limitations affect the availability of medical expertise as well as radiological and laboratory diagnostic services. These factors impact on key aspects of health care, including pathways of investigation, severity assessment, and the selection of empirical antimicrobial therapy. This review summarizes recent data from sub-Saharan Africa describing the burden, etiology, risk factors, and outcome of CAP. We describe the rational and context-appropriate approach to CAP diagnosis and management, including supportive therapy. Priorities for future research to inform strategies for CAP prevention and initial management are suggested.
Keywords: community-acquired pneumonia; sub-Saharan Africa; tuberculosis; HIV